Internalization of Ritual-Based Gratitude: An Ethnographic Study of Marhaban Culture Among Rural Youth - Handoko, Helmi; Kustanto, Juli; Amrillah, M Soinun; Oviyanti, Fitri; Maryamah; Hosaini, Hosaini (Jurnal Hadratul Madaniyah, 2026)
This study is motivated by limited research on the specific role of local religious wisdom in cultivating a grateful character, despite its significant impact on the context of adolescent personality formation amidst the challenges of modernization. This study aims to examine the role and mechanisms of the local Marhaban culture in cultivating a grateful character in adolescents in Jatimulyo Village. This study adopted a qualitative design, with religious leaders, parents, and youth groups in Jatimulyo Village selected through purposive sampling techniques. Data collection used participatory observation, in-depth interviews, and documentation and was analyzed through thematic analysis of an interactive model (data reduction, data presentation, and conclusion drawing). The findings reveal that the Marhaban tradition functions as an effective cultural-religious forum, where prayer recitation, Barzanji, and social interactions explicitly and implicitly teach the values ​​of respect, togetherness, and recognition of God’s blessings. Marhaban has an important and relevant role as an effective medium. dThe internalization of the character of gratitude (in the verbal, heart, and action aspects) in adolescents in the modern era. The implications include theoretical consistency, such as the development of literature on ethnopedagogy of religious character, and practical recommendations for community leaders and village program managers to optimize and institutionalize adolescent participation in Marhaban as an informal character education program. In addition, this study identifies future research opportunities on measuring the long-term impact of Marhaban on adolescent psychological resilience.